Beyond Unionism versus Nationalism: the Rise of the Alliance Party of Northern Ireland. Issue 2 (15th May 2020) - Tonge, Jonathan
Abstract: Northern Ireland has always been a polity noted for its strong links between national identity, religion, and voting, and acute British unionist versus Irish nationalist divisions. The constitutional question of whether Northern Ireland should be part of the UK or a united Ireland dominates. Yet, recent surveys have suggested a sizeable and growing section of its electorate declares itself neither unionist nor nationalist. This development may have assisted the growth of the centrist Alliance Party, which rejects unionist and nationalist identities and claims to be neutral on Northern Ireland's constitutional status. Alliance doubled its vote across three elections in 2019 and is now the third largest party in the region. This article examines the importance of ideological dealignment relative to other factors, such as Alliance's opposition to Brexit, in explaining the rise of a non‐binary party in a divided society.